IMPLEMENTASI MENDUKUNG KETAHANAN PANGAN MELALUI KEGIATAN M-KRPL DI KOTA KUPANG NUSA TENGGARA TIMUR - Nelson Hasdy Kario (Universitas Muhammadiyah Purwokerto, 2015)
Sustainable food house area (KRPL) is a governmental program to drive economy to maximize fulfillment of farmer’s food need. It was early introduced by Agricultural Ministry in Kayen Village, Pacitan, East Java by President Susilo Bambang Yudhoyono and then was developed by Agricultural Research agency in Indonesia by BPTP. Target area is yard. Kupang is one of town in NTT doing the activity. The objective of the research was to identify implementation of KRPL model in Kupang, to evaluate performance of technology component in KRPL activity and to identify obstacle and continuity of the program. The research was conducted in Kupang for six months from July–December 2013. The results indicated that the program was implemented in six areas (three military areas and three civil areas) with good results indicated with various plants cultivated such as horticulture, medicinal plant and ground fishery. Performance of component application has run as planned step from dissemination, preparation and realization (polybag filling, planting, transferring, keeping, harvest and post harvest). The dominant obstacles is water.